Pelatihan Pemasaran Produk Berbasis jejaring Media Sosial kepada Masyarakat Desa Curug Wetan - Rudy Pramono; Vasco Adato H, Rudyanto, Juliana (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Curug Wetan Tangerang community has an entrepreneurial desire, but does not yet know how to do product marketing. Therefore, the PKM team (lecturers and students) held a Training on How to Marketing Social Media Network Based Products to Kampung Curug Wetan Community organized by the Faculty of Tourism of the University of Pelita Harapan as a form of Community Service in the framework of the annual Hospitour 2019 program. The PkM team provided training to improve skills and capacity for business actors in Kampung Curug Wetan in marketing social media network-based products. The PkM team provides training to around 20 participants related to online product marketing by using social media networks that are very easy to use with small investments, but have a wide impact. The PkM method is used through skills training and direct assistance (face to face) with participants in Kampung Curug Wetan ,Tangerang The results of PkM activities are expected to increase understanding and skills on marketing methods through social media networks, especially using smartphone devices connected to the internet, so participants are able to make product packaging to be displayed on smartphone social media.